European Investigation Order – Selected Problems on Polish Implementation - Woźniewski, Krzysztof Wiesław (Review of European and Comparative Law, 2021)
The paper presents selected key problems of Directive 2014/41/EU regarding the European Investigation Order in criminal matters within the context of its Polish implementation in 2018. The paper focuses on the concept of investigative measures, administration of justice and exclusionary evidence rules as a limitation of issuing a Polish EIO. Additionally, the study attempts to approximate the reduced procedural mechanism in the context of issuing the ECI.